The Influence of Entrepreneurial Education and Psychological Capital on Entrepreneurial Behavior Among College Students - Cui, Jun (Frontiers in Psychology, 2021)
This research investigates the impact of entrepreneurial education (EE) on entrepreneurial behavior (EB) by unpacking how EE influences both psychological capital (PC) and EB, and how PC mediates the relationship between EE and EB. A cross-section survey data of 1405 college students in China was used to test the proposed mediating model. The research found that EE has a positive effect on EB; that EE has a positive effect on all four sub-constructs (hope, self-efficacy, resilience, and optimism) of PC; and that only self-efficacy positively correlated with EB while the other three components of PC do not have such correlations, and accordingly only self-efficacy mediates the relationship between EE and EB. This study contributes to a nuanced understanding of the multi-facet role of different components of PC in the prediction for EB, to expanding a novel impact type of EE from a psychological angle, and to the understanding of how psychological capital really works by unpacking its educational antecedent and behavioral consequent. The research also has practical implications for policy-makers, managers, and educators in entrepreneurial education.